1‐Alkali‐metal‐2‐alkyl‐1, 2‐dihydropyridines: Soluble Hydride Surrogates for Catalytic Dehydrogenative Coupling and Hydroboration Applications. Issue 66 (3rd November 2017) - McLellan, Ross; Kennedy, Alan R.; Mulvey, Robert E.; Orr, Samantha A.; Robertson, Stuart D.
Abstract: Equipped with excellent hydrocarbon solubility, the lithium hydride surrogate 1‐lithium‐2‐ tert ‐butyl‐1, 2‐dihydropyridine (1t Li) functions as a precatalyst to convert Me2 NH⋅BH3 to [NMe2 BH2 ]2 (89 % conversion) under competitive conditions (2.5 mol %, 60 h, 80 °C, toluene solvent) to that of previously reported LiN(SiMe3 )2 . Sodium and potassium dihydropyridine congeners produce similar high yields of [NMe2 BH2 ]2 but require longer times. Switching the solvent to pyridine induces a remarkable change in the dehydrocoupling product ratio, with (NMe2 )2 BH favoured over [NMe2 BH2 ]2 (e.g., 94 %:2 % for1t Li). Demonstrating its versatility, precatalyst1t Li was also successful in promoting hydroboration reactions between pinacolborane and a selection of aldehydes and ketones. Most reactions gave near quantitative conversion to the hydroborated products in 15 minutes, though sterically demanding carbonyl substrates require longer times. The mechanisms of these rare examples of Group 1 metal‐catalysed processes are discussed. Abstract : Cat family : Alkane soluble alkali metal 1, 2‐dihydropyridines, surrogate carrier complexes for molecular alkali metal hydride salts, are efficient main group catalysts for amine borane dehydrocoupling and hydroboration of carbonyl substrates.